135k views
1 vote
Simplify the given equation.

6 - (3x + 10) + 4(2 - x) = 15

Options:
4 - 7x = 15
4 - 4x = 15
12 - 7x = 15

PLEASE, I'm begging you, PLEASE explain step-by-step how to get to your answer. Please don't just give me the answer and not explain anything, I'm begging you

1 Answer

5 votes

6 - (3x+10) + 4(2-x)=15

6- (3x +10) + 8-4x = 15. ( opening brackets)

-3x - 4x= 15 - 6-8. ( keeping all x terms on left and moving numbers to the right)

-7x = 1

x= 1/-7

Hope this helps:)

User Hurda
by
4.9k points